(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Diffusion of culture and for all round development of a nation for example improvement of education, health, economic development, and social and domestic purpose well connected transportation network system is necessary. But sometime we are facing so many different kinds of physical, economic, social and cultural problems when fall in a traffic congestion due to a lot of reason. Traffic jam is a common fact to the local people of domohani village. Lack of proper monitoring or due to violating norms they have to face ten to fifteen times traffic congestion daily from 9am to 6pm. This paper basically deals with the nature, impact ,causes and probable solution of that’s kind of traffic congestion of domohani bazar in Baraboni C.D Block in Asansol sadar sub division of Paschimin Bardhaman district of West Bengal .. The paper also suggests a batter plan or alternative proposal to minimize frequent type of congestion to this area.